Inovasi Usaha Abon Lele Tingkat Usaha Kecil Menengah (UKM) dalam Peningkatan Kualitas Produk - Anam, Choirul; Harini, Harini; Widiyanti, Emi (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2022)
Industrial development in Indonesia is very dynamic, including in the food and beverage industry. So that innovation and facilitation for Small and Medium Enterprises (SMEs) are needed to improve the competitiveness of the products produced. SMEs shredded catfish "Indri Marwanti" Mojolaban Sukoharjo, is one of the fisheries product processing industries that have made innovations in shredded catfish products. Starting from the arrangement of facilities and production equipment, the application of good manufacturing practice methods, adaptive use of equipment to improve product quality, to packaging design and labeling on its business products. This activity is intended to implement innovations in increasing the quantity and quality of SME  shredded Catfish "Indri Marwanti" through improving production methods and introducing several equipment and packaging that can improve the quality of shredded catfish so that consumer acceptance and business turnover can increase.